Role of entities of human resource management in personnel controlling - Kuźniarska, Aneta; Stańczyk, Izabela (Contemporary organisation and management. Challenges and trends, 2020)
At present personnel controlling is becoming increasingly applied as a tool in the management of various areas in an organization. The herein paper presents the essence of personnel controlling applied in the field of HR, its division in terms of the nature of tasks and levels of management for operational and strategic controlling. The role played by the entities of human resource management in terms of the functioning of personnel controlling is worthy of attention. The authors at hand present their research results in this sphere. The research sample encompassed employees in managerial and non-managerial positions in terms of executing their tasks in retail trade chains. Survey research was conducted as a method of research.